Exploring Students’ Reading Ability in An Extensive Reading Class Through Constructivism of Narrative Text - Fadillah, Zikry Indra; Kamil, Acep Bahrum; Wachyudi, Kelik (JIIP - Jurnal Ilmiah Ilmu Pendidikan, 2022)
The level of understanding of reading English narrative texts at the junior high school level still needs to be given extra learning. There are many factors that prevent students from understanding the narrative text, one of which is students who have difficulty understanding English words in narrative texts. This study uses the theory of constructivism, namely two-way learning carried out by the teacher and the students in the class. This research uses a qualitative method, in which the researcher uses research by means of classroom observations, and interviews in an effort to obtain data at school. The participants in this study were eighth grade students in one of the public schools in Bekasi Regency, West Java. The selected students are representatives of several students in the learning group. The results of this study are, there are some students who still do not master and understand the narrative legend text using constructivism techniques.